Pengaruh Kualitas Produk dan Kualitas Pelayanan Terhadap Kepuasan Pengunjung di MD Burger Bar Canggu - Jaya, Gusti Ngurah Prana; Susila, I Made Gede Darma; Dewi, Desak Made Purnama (Universitas Triatma Mulya, 2025)
The purpose of this study is to determine the product quality and service quality on visitor satisfaction, this study uses accidental sampling technique. The data used are primary data derived from questionnaires of 98 respondents, then the questionnaire was tested using validity and reliability tests followed by classical assumption tests and hypotheses were proven using multiple linear regression analysis to measure the effect of each independent variable on the dependent variable processed with the SPSS (Statistical Package for Social Science) version 22. The results of the analysis show a regression model Y = 1,800 + 0.109X1 + 0.247X2, the conclusion obtained is that product quality (X1) partially has a positive and significant effect on visitor satisfaction at MD Burger Bar Canggu which is indicated by the positive b1X1 regression coefficient. Service quality (X2) partially has a positive and significant effect on visitor satisfaction, this can be seen in the positive b2X2 regression coefficient. The results of the hypothesis test state that, H1, the product quality variable has a t-value of 3.580, greater than the t-table of 1.98525 and obtained a significance value of 0.001, smaller than the 0.05 significance level (0.001 < 0.05), which means that product quality has a positive and significant influence on customer satisfaction. H2, the service quality variable has a t-value of 7.435, greater than the t-table of 1.98525 and obtained a significance value of 0.000, smaller than the 0.05 significance level (0.000 < 0.05), which means that service quality has a positive and significant influence on customer satisfaction at MD Burger Bar Canggu.